2013
DOI: 10.1111/j.1745-7599.2012.00779.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of demographic, psychosocial, and clinical characteristics among younger and older persons with acute coronary syndrome

Abstract: Clinicians need to be persistent in promoting the importance of weight loss and smoking cessation. Screening and treating depression in younger persons is a prudent approach. The significance of regular screening and aggressive treatment of other risk factors (i.e., diabetes, hypertension, and dyslipidemia) should not be overlooked.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…Although overall survival is expected to be lower with age, studies have shown that younger patients may be more susceptible to depression. 29,30 We had missing data that we replaced with multiple imputation. Data collected in-hospital came from a register collected for routine purposes; thus, we can assume that missingness occurs completely at random.…”
Section: Discussionmentioning
confidence: 99%
“…Although overall survival is expected to be lower with age, studies have shown that younger patients may be more susceptible to depression. 29,30 We had missing data that we replaced with multiple imputation. Data collected in-hospital came from a register collected for routine purposes; thus, we can assume that missingness occurs completely at random.…”
Section: Discussionmentioning
confidence: 99%
“…In our recent investigation (n=1140) [27], younger ACS patients (males ≤50 years of age and females ≤55 years of age) were more likely to feel depressed during the year preceding their admission for ACS (p<0.001) compared to their older counterparts. In that same study, younger patients were less likely to be dyslipidemic, hypertensive (p<0.001 for each), or diabetic (p=0.025) than older patients.…”
Section: Discussionmentioning
confidence: 99%
“…This is probably due to the younger age of the study participants. Indeed, in our previous investigation (n=1140) [17], compared to their older counterparts, younger ACS patients (males ≤50 years of age and females ≤55 years of age) were significantly more likely to have a higher BDI-II depression score, and to feel depressed during the year preceding their admission for ACS. Importantly, in one study [19], after adjustment for disease severity and comorbidities, somatic symptoms of depression and hopelessness were associated with poor post-MI prognosis in younger, but not in older patients.…”
Section: Discussionmentioning
confidence: 99%
“…While ACS occurs more frequently at an older age, younger patients (males ≤50 years of age and females ≤55 years of age) constituted 20% of the total sample in a recent large study (n=1140) of consecutively admitted ACS patients (age range 26–96 years), [17]. This is an important finding, given the results of the few studies of ACS patients that specifically examined younger patients.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation